2016
DOI: 10.1109/tns.2016.2537643
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the SEE Sensitivity of a 45 nm SOI Multi-Core Processor Due to 14 MeV Neutrons

Abstract: Abstract-The aim of this work is to evaluate the SEE sensitivity of a multi-core processor having implemented ECC and parity in their cache memories. Two different application scenarios are studied. The first one configures the multi-core in Asymmetric Multi-Processing mode running a memory-bound application, whereas the second one uses the Symmetric Multi-Processsing mode running a CPU-bound application. The experiments were validated through radiation ground testing performed with 14 MeV neutrons on the Free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The validation of the proposed approach was done by SWIFI, which is a useful technique to emulate SEU effects. The adopted approach was proven in our previous works concerning fault-injection for multi-core processors [7,[37][38][39]. It is important to note that the objective of this approach is to reproduce the SEUs effects, which are bit-flips in memory cells caused by natural radiation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The validation of the proposed approach was done by SWIFI, which is a useful technique to emulate SEU effects. The adopted approach was proven in our previous works concerning fault-injection for multi-core processors [7,[37][38][39]. It is important to note that the objective of this approach is to reproduce the SEUs effects, which are bit-flips in memory cells caused by natural radiation.…”
Section: Resultsmentioning
confidence: 99%
“…The fault-injection technique proposed in this approach to emulate SEU is an SWIFI technique. As was previously stated, the approach validated in our previous works concerning fault-injection on multi-core processors [7,[37][38][39] is based on Code Emulated Upset (CEU) principles [47], which reproduce, without intrusion, the effects of SEUs. This is achieved by the assertion of asynchronous interrupt signals.…”
Section: Fault-injection Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…e dynamic asymmetric multiprocessing (AMP) tests have demonstrated that in spite of parity and ECC protection mechanisms, errors have been occurred in the result of the application. In addition, it can be seen that the dynamic sensitivity of the device strongly depends on the implemented multiprocessing mode [14].…”
Section: Related Workmentioning
confidence: 99%
“…Reference [23] evaluates the dynamic sensitivity of different scenarios running on the Freescale P2041 multi-core. This work illustrates that a 45 nm Silicon-On-Isolator (SOI) quad-core processor is about four times less sensitive to SEE than its CMOS (Complementary Metal-Oxide Semiconductor) counterpart when the devices are evaluated under 14 MeV neutron energy.…”
Section: Introductionmentioning
confidence: 99%